Fatigue performance of flexible pavements with cement-bound granular material (CBGM) (Fracture and Structural Integrity, 2025)
The article analyzes the fatigue performance of flexible pavement structures incorporating cement-bound granular material (CBGM) as a subbase layer. In current Polish design methodologies, overly conservative and underestimated stiffness modulus values are often assumed for CBGM, neglecting the material’s behavior in the uncracked state. A mechanistic analysis was conducted using the theory of multilayer elastic half-space. Fatigue life was evaluated based on two criteria: Dempsey and De Beer. The results showed that, according to Dempsey’s criterion, only one selected layer configuration would not crack under construction traffic, whereas De Beer’s criterion indicated that none of the analyzed structures should fail. The findings demonstrate a significant reserve in the fatigue life of CBGM layers and highlight the need to revise existing design assumptions, particularly for mixtures of lower strength classes.
Keywords: fatigue life; Flexible pavement; Cement-bound granular material; Mechanistic design; Stiffness modulus